A New Voice for an Ancient Story: Speaking from the Margins of Homer’s Iliad in Madeline Miller’s The Song of Achilles - Maria Antonietta Struzziero (Anglica. An International Journal of English Studies)
Madeline Miller’s The Song of Achilles (2011) is an imaginative rewriting of Homer’s Iliad. The writer uses the strategy of transfocalization and enters the text from the point of view of Patroclus. His fresh look offers a new critical perspective both on the moral world of the epic and on Achilles, the great Greek hero whose complex personality and tragic hubris Patroclus observes with emotional understanding. Miller transforms the Homeric sparing narrative of the friendship between Patroclus and Achilles into a touching love story built on their mutual devotion, and locates this narrative at the heart of a world of ruthless violence. This paper will consider the writer’s use of hypertextual adaptation in the novel from the perspective of the change in the narrative focus of the source, and discuss her objectives and methodology.